Local Governments' Fiscal Balance, Privatization, and Banking Sector Reform in Transition Countries - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2012)
Several transition economies have undertaken fiscal decentralization reforms over the past two decades along with liberalization, privatization, and stabilization reforms. Theory predicts that decentralization may aggravate fiscal imbalances, unless the right incentives are in place to promote fiscal discipline. This paper uses a panel of 20 transition countries over 19 years to address a central question of fact: Did privatization help to promote local governments' fiscal discipline? The answer is clearly 'no' for privatization considered in isolation. However, privatization and subnational fiscal autonomy along with reforms to the banking system - restraining access to soft financing - may prove effective at improving fiscal balances among local governments.